Flipping the Script from Talking to Teens about "Celebrating Diversity" to Promoting Equity Through Embracing Vulnerability and Enacting Courage. (3rd April 2017) - Bettez, Silvia
Abstract : Diversity and inclusion are popular, yet often challenging, topics for youth in schools. A common approach to address the issues is to invite outside speakers to discuss ways to "celebrate diversity." After being invited to give such a talk, I created and enacted a presentation at an affluent high school on this topic that is grounded in social justice education. The presentation flips the script from celebrating diversity to promoting equity by using a framework that connects embracing vulnerability with enacting courage. This article provides the theoretical underpinnings of this embodied approach. The presentation maneuvers include definitions of courage as connecting with others while embracing vulnerability; modeling the approach through shared personal counternarratives; defining related social justice terms and concepts; sharing counternarratives of young people; and providing an example of ways (in this case, promoting alliances) to create connections to promote equity. This approach can be a starting point to deeper understandings of inequity. The approach has the potential to encourage young people to embrace the marginalized parts of their identities and take actions against discrimination and oppression.